2005
DOI: 10.12968/jowc.2005.14.6.26793
|View full text |Cite
|
Sign up to set email alerts
|

Study to determine the efficacy of topical morphine on painful chronic skin ulcers

Abstract: The results suggest that topical morphine cannot be an alternative to morphine administered by other routes (subcutaneously or orally) in painful chronic skin ulcers. Stimulation of peripheral morphine receptors by systemic morphine could explain the difference between these results and those of previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 16 publications
1
32
0
3
Order By: Relevance
“…However, Vernassiere etal. (10) recently concluded that topical morphine, cannot be an alternative to morphine administered by other routes in painful chronic skin ulcers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Vernassiere etal. (10) recently concluded that topical morphine, cannot be an alternative to morphine administered by other routes in painful chronic skin ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid receptors have been identified in peripheral tissues and it has been suggested that topically applied opioids may have a local action (9)(10). Opioid receptors are not obvious in normal tissue, but appear within minutes to hours after the start of an inflammatory process (9,11).…”
mentioning
confidence: 99%
“…Apesar de terem sido encontrados recetores opioides μ em nociceptores periféricos, os resultados de ensaios clínicos são desanimadores e, até à data, não foi demonstrada eficácia analgésica com esta abordagem. 41,45,46 Mais recentemente, o sevoflurano (um anestésico geral inalatório) em formulação tópica mostrou ser uma alternativa promissora para a analgesia de longa duração na UP.…”
Section: Nevralgia Pós-herpéticaunclassified
“…For example, a randomized controlled trial comparing the use of topical morphine sulfate versus traditional Jelonet dressings in burn patients revealed increased need of rescue analgesia and higher pain scores in the topical morphine group [84]. Another study revealed no significant reduction in pain with patients with skin ulcers when topical morphine was compared to placebo [85]. However, in patients with mucositis undergoing chemoradiotherapy for head and neck cancer, oral morphine mouthwash has been shown to significantly reduce pain and reduce length of functional impairment [86] In summary, topical analgesics may provide additional analgesia in patients who may not be able to tolerate the adverse effects of systemic analgesics.…”
Section: Topical Analgesicsmentioning
confidence: 99%